Estimate of TB incidence and a critical analysis of programmatic data of TB score from Sub national Certification survey of district Niwari, M.P., India - Ghanshyam Ahirwar; Manohar Bhatia; Vikas Pandey; Bikramjeet Mitra; Yogesh Sharma; Varsha Rai (Journal of Family Medicine and Primary Care)
Background: India accounted for 26% of the global tuberculosis (TB) burden in 2023, with 27 lakh cases reported and 89% treatment coverage. Madhya Pradesh, a high-burden state, reported 28,299 cases in 2023. The Government of India aims to eliminate TB by 2025 through the Strategic National Campaign (SNC), emphasizing surveillance, early diagnosis, and comprehensive care. This study evaluates TB management trends in the Niwari district, Madhya Pradesh, a tribal region, from 2018 to 2022. Objectives: To estimate TB incidence, validate claims for TB-free status during SNC surveys, and analyze TB score trends in the Niwari district. Materials and Methods: This retrospective, cross-sectional study utilized data from the National Tuberculosis Elimination Programme (NTEP), including records from the District Tuberculosis Officer (DTO), treatment cards, laboratory registers, and the Ni-kshay portal. Seven TB score parameters were analyzed: notification, HIV screening, UDST, and treatment success. TB incidence was calculated per 100,000 population over five years (2018-2022). Ethical clearance was obtained. Results: TB notification improved from 59.6% to 83.3%, with 97% HIV screening by 2022. UDST peaked at 112.5% in 2020. Treatment success rates ranged from 80.6% to 87.6%. However, Nikshay Poshan Yojana beneficiary payments declined from 87.5% in 2021 to 49.4% in 2022. TB incidence fluctuated, from 129 per lakh (2018) to 143 per lakh (2022), reflecting improved detection post-COVID-19. Verified data closely matched reported data by 2022. Conclusion: Niwari district has made significant progress in TB management, particularly in notification and HIV screening, but challenges persist in sustaining financial support and addressing operational inefficiencies. Continued community engagement, advocacy, and SNC rounds are crucial for achieving TB elimination by 2025.